Literature Analysis of IoT Application to Increase Oyster Mushroom Production Efficiency through Automatic Temperature Monitoring - Ida Farida; Maulana Sayyidina Kahfi; Muhamad Pardi (Publikasi Indonesia, 2025)
Oyster mushroom cultivation requires strict temperature and humidity control for optimal yields, yet conventional monitoring methods often lead to fluctuations that compromise production efficiency. This literature review aims to analyze the application of Internet of Things (IoT) technology for automated environmental monitoring and its impact on oyster mushroom production efficiency. Using a systematic literature review methodology, 15 relevant studies published between 2013 and 2023 were analyzed from databases including Google Scholar, IEEE Xplore, and Scopus. The analysis reveals that IoT systems utilizing microcontrollers (Arduino/NodeMCU), DHT11/DHT22 sensors, and automated actuators (fans, mist pumps) successfully maintain optimal growing conditions (temperature: 22–30°C, humidity: 70–95%). This technological implementation demonstrates significant production improvements, including yield increases of up to 40%, labor time reduction exceeding 70%, and enhanced mushroom quality with a higher proportion of Grade A harvests. These findings highlight IoT’s potential to revolutionize oyster mushroom cultivation through precision agriculture, offering a viable pathway for sustainable intensification in mushroom farming, particularly in resource-constrained settings where production stability is challenging to maintain.